The impact of COVID‐19 in the management of AL amyloidosis and Immunoglobulin Deposition Disease: A single‐center experience. (29th November 2020) - Lee, Holly; Tay, Jason; Duggan, Peter; McCulloch, Sylvia; Neri, Paola; Bahlis, Nizar J.; Jimenez‐Zepeda, Victor H.
Abstract: Introduction: Patients with AL amyloidosis and immunoglobulin deposition diseases (IDD) are vulnerable during the COVID‐19 pandemic due to the immune compromise from the plasma cell disorder and therapy‐related immune defects. We describe a local experience in providing care for patients with AL amyloidosis and IDD. Method: Patient treatment and disease status since the beginning of the pandemic on March 11, 2020, as declared by WHO, were collected and analyzed. Results: Ninety‐six patients with AL amyloidosis and IDD were included. Four patients with IDD and 22 patients with systemic AL amyloidosis were receiving treatment during the pandemic. Since the pandemic, patients' treatments were discontinued if they achieved VGPR or better postinduction. Seven patients discontinued all treatment after achieving VGPR, and others required treatment modifications. 28 patients have been tested for COVID‐19, and all tests have been negative. Three patients died since the pandemic, two from organ complications of systemic AL amyloidosis and one from an unrelated cause. Conclusion: The management of AL amyloidosis and IDD must be individualized on the clinical characteristics, centers' access to care under the pandemic restrictions, and the epidemiological aspects of the outbreak.